Serum amyloid A proteins reduce bone mass during mycobacterial infections - Gomes, Ana Cordeiro; Sousa, Daniela Monteiro; Oliveira, Tiago Carvalho; Fonseca, Óscar; Pinto, Ricardo J.; Silvério, Diogo; Fernandes, Ana Isabel; Moreira, Ana C.; Silva, Tânia; Teles, Maria José; Pereira, Luísa; Saraiva, Margarida; et al. (Frontiers in Immunology, 2023)
Osteopenia has been associated to several inflammatory conditions, including mycobacterial infections. How mycobacteria cause bone loss remains elusive, but direct bone infection may not be required. Using genetically engineered mice and morphometric, transcriptomic and functional analyses, we found that infection with Mycobacterium avium impacts bone turnover by decreasing bone formation and increasing bone resorption, in an IFN- and TNF-dependent manner. IFN produced during infection enhanced macrophage TNF secretion, which in turn increased the production of serum amyloid A (SAA) 3. Saa3 expression was upregulated in the bone of both M. avium- and M. tuberculosis-infected mice and SAA1 and 2 proteins (that share a high homology with murine SAA3 protein) were increased in the serum of patients with active tuberculosis. Furthermore, the increased SAA levels seen in active tuberculosis patients correlated with altered serum bone turnover markers. Additionally, human SAA proteins impaired bone matrix deposition and increased osteoclastogenesis in vitro. Overall, we report a novel crosstalk between the cytokine-SAA network operating in macrophages and bone homeostasis. These findings contribute to a better understanding of the mechanisms of bone loss during infection and open the way to pharmacological intervention. Additionally, our data and disclose SAA proteins as potential biomarkers of bone loss during infection by mycobacteria.